Coyote Ugly [videorecording (DVD)] - Perabo, Piper; Bello, Maria, 1967-; Lynskey, Melanie; Garcia, Adam, (Adam Gabriel); Goodman, John, 1952- (Touchstone Home Entertainment, 2001)
A shy, innocent girl new to New York City gets a job as one of the barmaids at the hottest nightclub in town.